Taxonomy of Simulium (Inaequalium) petropoliense Coscarón (Diptera: Simuliidae) from Brazil, with the first description of the male and larva - Hernandez, Luis Miguel; de Luna Dias, Antonio Paulino Andrade; Maia-Herzog, Marilza; Shelley, Anthony John (Zootaxa, 2006)
We describe the male and larva of Simulium petropoliense for the first time and redescribe the female and pupa. All morphological characters are fully illustrated and comparisons with closely related species are given.